Virtual senior university as a promoter of sustainability and the democratization of education - satisfaction and continuity - Galinha, Sónia Alexandre (2021)
Currently, Portugal is the fifth most aged country in the world, and it is expected to reach third position by 2030. Aware of this reality, civil society has organised itself in the most varied ways in an attempt to fill the non-existent answers. The seniors universities are an example of this, seeking to provide all their students with recreational activities where socialising is surely one of the most important weapons in the fight against isolation and depressive conditions with particular incidence in this younger population. The COVID-19 pandemic has worsened this not very encouraging scenario. Aware of this reality and for the pandemic period, senior universities have launched the Virtual Senior University project, as an extension of face-to-face teaching into virtual teaching. Based on a random sample of one hundred students enrolled in the Virtual Senior University (VSU) project, a quantitative, cross-sectional and correlational study was conducted using a demographic questionnaire and the QOSUSV scale in order to evaluate the participation and experience of VSU students in the activities carried out during the first period of confinement.The analysis of the results revealed that the USV offer is inclusive, transversal and covers the whole country. USV proved to be a contribution to sustainability in education, particularly in periods of confinement and emergency. Additionally the activity that deserved a greater welcome by students was all existing offers (23,93%); the most frequently mentioned difficulty was: accessing the internet and mastering the devices and then class schedules. A significant proportion of students (69%) stated that they had nothing negative to point out, which reinforces the satisfaction with VSU previously questioned (98%). The interest in continuing the VSU project in the next academic year was expressed by 83% of the students, a fact evidenced by the positive (rho=0.596) and statistically significant (p<0.01) correlation between satisfaction and the desire to continue VSU for the following academic year.